Psychiatric Comorbidities and BMI: An Exploratory Analysis. (2nd September 2017) - Guenzel, Nicholas; Schober, Daniel J.
ABSTRACT: Years of research and clinical practice have demonstrated that individuals with certain mental health conditions are at an increased risk of obesity. However, no identified research has examined associations between multiple comorbid psychiatric disorders and body mass index (BMI). This study uses a secondary analysis to examine associations between a large number of combinations of various mental health conditions and BMI. Surprisingly, the results of this study indicate that the most comorbid psychiatric disorders are not associated with an increased risk of elevated BMI. However, bipolar disorder, agoraphobia, attention-deficit hyperactivity disorder, and panic disorder had the greatest number of comorbid disorder associations linked with elevated BMI. The effect sizes ranged from a significant but relatively small Cohen's d of 0.3 to a more notable effect size of 0.7. The results of this study indicate that practitioners should be especially vigilant in helping their patients to avoid weight gain when they have one of the four identified disorders in combination with at least one other disorder. Future research is needed to understand the mechanisms underlying this increased risk and evaluate targeted interventions that would be the most effective for people with these diagnoses.